Association of interleukin 18-607A/C and -137C/G polymorphisms with oxidative stress in renal transplant recipients. (27th May 2016) - Davran, Fatih; Yilmaz, Vural Taner; Erdem, Bilge Karatoy; Gultekin, Meral; Suleymanlar, Gultekin; Akbas, Halide
Abstract: Objectives IL-18 mediates various inflammatory and oxidative responses including renal injury, fibrosis, and graft rejection. It has been reported that the promoter -607 and -137 polymorphisms of IL-18 influence the level of IL-18. This prospective observational study investigated the association between oxidative stress with IL-18-607 and -137 polymorphisms in renal transplant recipients.Patients and methods This study included 75 renal transplant recipients (28 female, 47 male) from living-related donors. Blood samples were collected immediately before and after transplantation at day 7 and month 1. Serum IL-18, creatinine, cystatin C, CRP, and oxidative stress markers (TOS, TAC) were measured. The Oxidative Stress Index (OSI) was calculated. Polymorphisms of the promoter region of the IL-18 gene, IL18-607A/C, and -137C/G were determined by analysis of a "real-time PCR/Melting curve".Results Serum creatinine, cystatin C, CRP, IL-18, TOS, and OSI levels significantly decreased after transplantation. Post-transplant levels of serum TAC and estimated GFR demonstrated consistent significant increases. Serum IL-18 levels were significantly higher in patients with IL-18-137 GG and IL-18-607 CC genotypes before transplantation.Conclusion Our results indicate that the IL-18-137 GG and -607 CC genotypes contribute to higher IL-18 levels; however, the influence of these polymorphisms on oxidative stress has not been observed.